Optimization of Short-Lag Spatial Coherence Imaging Method - Jakub DOMARADZKI; Marcin LEWANDOWSKI; Norbert ŻOŁEK; Marcin LEWANDOWSKI (Archives of Acoustics, 2019)
The computing performance optimization of the Short-Lag Spatial Coherence (SLSC) method applied to ultrasound data processing is presented. The method is based on the theory that signals from adjacent receivers are correlated, drawing on a simplified conclusion of the van Cittert-Zernike theorem. It has been proven that it can be successfully used in ultrasound data reconstruction with despeckling. Former works have shown that the SLSC method in its original form has two main drawbacks: time-consuming processing and low contrast in the area near the transceivers. In this study, we introduce a method that allows to overcome both of these drawbacks.